Diagnostic value of cerebrospinal fluid markers and clinical profiles in distinguishing tuberculous from pyogenic meningitis: a cross-sectional study - Rangashamaiah, Arun Baraguru; Ajay,; Gang, Prachi (International Journal of Research in Medical Sciences, 2026)
Background: Tuberculous meningitis (TBM) and pyogenic meningitis (PM) are significant etiologies of central nervous system infections necessitating immediate and precise differentiation owing to their distinct treatment protocols and prognostic outcomes. The similar symptoms of these two types of meningitis often make it hard to diagnose them early. Methods: This cross-sectional study (CSS) assessed cerebrospinal fluid (CSF) markers and clinical profiles in patients diagnosed with TBM and PM. We looked at the cytological parameters, protein, glucose, adenosine deaminase (ADA), and lactate levels in the CSF. We also did electrophoretic protein fractionation. Clinical data and neuroimaging results were documented to discern distinguishing characteristics. Results: TBM cases exhibited lymphocytic pleocytosis, elevated ADA levels, increased protein-glucose ratios, and heightened gamma globulin fractions on electrophoresis. On the other hand, PM showed a lot of neutrophils, a lot of CSF lactate, and more alpha globulin fractions. Hydrocephalus and cranial nerve involvement were more prevalent in TBM. These parameters exhibited high sensitivity and specificity in distinguishing TBM from PM. Conclusion: The combination of CSF biochemical markers, cytological profiles, electrophoretic patterns, and clinical features improves the accuracy of diagnosing TBM and PM. This multiparametric method is very useful in places where resources are limited because it helps people get the right treatment at the right time to improve their health.